Mediation Model of Strategic Foresight Influencing Dynamic Capability - Siti Azirah Asmai,; Ali Almansoori, Bakheeta Saeed; Kamalrudin, Massila (International Journal of Sustainable Construction Engineering and Technology, 2022)
Strategic Foresight (SF) is required for an organisation in facing Volatility, Uncertainty, Complexity and Ambiguity (VUCA) environment to maintain relevant in future. There are many studies on application of SF by organisations in preparing for the unexpected. Especially, the relationship between SF and dynamic capabilities (DC) of an organisation. Thus, this study developed a mediation model which comprises of five exogenous constructs namely environmental scanning (ES); scenario planning (SP); knowledge creation (KC); culture (CU) and formal organization (FO), one endogenous construct of dynamic capabilities and one mediator construct of organisational learning capability (OLC). The data use to develop the model was derived from 209 respondents that participated in the questionnaire survey. The respondents were selected using a purposive random sampling technique amongst individuals who involved in decision-maker position of UAE organizations. The model was evaluated at measurement and structural components to achieve the fitness criteria values. It was found that the model has achieved GoF value of 0.8423 which indicates high overall validating power. This means that the model is rated as a high-quality model. After achieving these fitness criteria, hypothesis testing was conducted through bootstrapping function of the software. It was found that only two out of five of the direct effect relationships are significant, which are knowledge creation and formal organisation have significant relationships with the dynamic capabilities of the organisations. For mediation/indirect effect, it was found that organisational learning capacity as the mediator has significant effects toward three relationships which are scenario planning with dynamic capabilities; culture with dynamic capabilities and formal organisation with dynamic capabilities.